Pulmonary hypertension - Andrew Peacock (European Respiratory Review, 2013)
2011 to 2012 has seen an explosion in published research in the field of pulmonary vascular disease, especially pulmonary hypertension. In conjunction with this research has been an explosion in clinical interest in treating pulmonary hypertension. This is possible because we now have three different generic classes of drug therapy: endothelin receptor antagonists, phosphodiesterase-5 inhibitors and prostacyclins. Clearly, however, we need to be careful that we are treating the correct disease with the correct drug and measuring the correct response. Herein, I will review the papers published over the last year that offer the most insight into the pathobiology, but also those that give us the clinical information we need in epidemiology, treatment and end-points so that we can treat this devastating group of disease.